Maternal characteristics associated with the fetal macrosomy diagnosis in a hospital III-1 of the capital of Peru: Características maternas asociadas al diagnóstico de macrosomía fetal en un hospital III-1 de la capital de Perú - Huacachi-Trejo, Kelly (2019)
Objective: To identify the maternal characteristics associated with the diagnosis of fetal macrosomia at Sergio E. Bernales Hospital from January to December 2018. Methods: An observational, analytical, retrospective, case-control study was carried out. The population studied was pregnant women with a diagnosis of fetal macrosomia treated in the gynecoobstetrics service of Sergio E. Bernales Hospital from January to December 2018. Through a data collection sheet, the information from the medical records was extracted; the data was then processed according to the IBM SPSS Statistics v25 program. Results: Of 532 patients studied, 133 cases and 399 controls were obtained. Maternal age varies between 14 and 45 years (average age of 27.01). A statistically significant association was found between fetal macrosomia and the following variables: post-term pregnancy (OR = 13,613 95% CI 2,901-63,891), gestational diabetes (OR 5.7 IC95% 2.5 -12.7), excessive weight gain (OR 1,833 95% CI 1,154-2,911), sex of the newborn (OR 1.83 95% CI 1.2-2.7) and age of the mother (OR 1.7 95% CI 1.0-2.9). When performing the multivariate analysis, no association was found with the variables age of the mother (P = 0.228, OR 1.510 95% CI 0.773-2.950) and BMI (P = 0.331, OR 0.740 95% CI 0.403-1.358), so they were considered confusing variables. Conclusion: The maternal characteristics associated with the diagnosis of fetal macrosomia are post-term delivery, gestational diabetes, excessive weight gain and sex of the newborn.